Role of microRNAs in intervertebral disc degeneration (Review) - Yang, Fengguang (Exp Ther Med, 2021)
The incidence of lower back pain caused by intervertebral disc degeneration (IDD) is gradually increasing. IDD not only affects the quality of life of the patients, but also poses a major socioeconomic burden. There is currently no optimal method for delaying or reversing IDD, mainly due to its unknown pathogenesis. MicroRNAs (miRNAs/miRs) participate in the development of a number of diseases, including IDD. Abnormal expression of miRNAs in the intervertebral disc is implicated in various pathological processes underlying the development of IDD, including nucleus pulposus (NP) cell (NPC) proliferation, NPC apoptosis, extracellular matrix remodeling, inflammation and cartilaginous endplate changes, among others. The focus of the present review was the advances in research on the involvement of miRNAs in the mechanism underlying IDD. Further research is expected to identify markers for early diagnosis of IDD and new targets for delaying or reversing IDD.